2022
DOI: 10.3390/ijms232315414
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote Dopamine Transporter Knockout Rats Display Enhanced Cocaine Locomotion in Adolescent Females

Abstract: Cocaine is a powerful psychostimulant that is one of the most widely used illicit addictive. The dopamine transporter (DAT) plays a major role in mediating cocaine’s reward effect. Decreases in DAT expression increase rates of drug abuse and vulnerability to comorbid psychiatric disorders. We used the novel DAT transgenic rat model to study the effects of cocaine on locomotor behaviors in adolescent rats, with an emphasis on sex. Female rats showed higher response rates to cocaine at lower acute and chronic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 96 publications
3
6
0
Order By: Relevance
“…We observed a strong effect of cocaine on these epigenetic enzymes in a sexand genotype-dependent manner. These results support our previous study [11], which showed robust sex differences in response to cocaine administration in DAT transgenic rats. Additionally, these data highlight the impact of partial or full DAT mutation on epigenetic enzymes and subsequent effects on cocaine-related behavior.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed a strong effect of cocaine on these epigenetic enzymes in a sexand genotype-dependent manner. These results support our previous study [11], which showed robust sex differences in response to cocaine administration in DAT transgenic rats. Additionally, these data highlight the impact of partial or full DAT mutation on epigenetic enzymes and subsequent effects on cocaine-related behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Cocaine was administered intraperitoneally (ip) for 8 days. The cocaine dose (0 or 10 mg/kg) was chosen based on previous publications [11,[68][69][70]. Saline 0.9% solution was used as vehicle.…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the observed tendency to δ lower value in DAT-HT rats can be interpreted as some motor facilitation of operant responding. Several papers have shown differences in locomotion of DAT-HT versus -WT littermates (Cristiana et al, 2020; Manoni et al, 2022; Pardo et al, 2022), so further studies are needed to better investigate the behaviour of heterozygous rats.…”
Section: Discussionmentioning
confidence: 99%